English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

This is how far I got...
sqrt 1/ sqrt 2 ( 2 sqrt2 + sqrt 2)
sqrt2(1) / sqrt 2(sqrt2) x 3 sqrt 2
sqrt2 / 2 (3 sqrt 2)

now what?

2007-04-03 08:13:02 · 5 answers · asked by jinglexjangle 1 in Science & Mathematics Mathematics

5 answers

1. sqrt (1/2)[sqrt(8) + sqrt(2)]
2. 1/sqrt(2)[2sqrt(2) + sqrt(2)]
3. 1/sqrt(2)[3sqrt(2)]
4. 3sqrt(2)/sqrt(2)
5. 3
The answer is 3

2007-04-03 08:21:29 · answer #1 · answered by Danyal Ali 1 · 0 0

sqrt 1/ sqrt 2 ( 2 sqrt2 + sqrt 2)=
(2sqrt2)/sqrt2 + (sqrt 2)/(sqrt 2)=
2 +1 = 3

2007-04-03 15:19:55 · answer #2 · answered by jaybee 4 · 0 0

first multiply the sqrt (1/2) into the paranthesis

sqrt (1/2) * sqrt (8) = sqrt (4) = 2

sqrt (1/2) * sqrt (2) = sqrt (1) = 1

so you get (sqrt(4) + sqrt(1)) = 3

3 is the simplified

2007-04-03 15:18:52 · answer #3 · answered by Anonymous · 0 0

sqrt (1/2) * (sqrt 8 + sqrt 2) = sqrt(2)/2 * 3sqrt 2 = 3*sqrt(2)*sqrt(2)/2 = 3*sqrt(2)^2/2 = 3*2/2 = 3

2007-04-03 15:18:20 · answer #4 · answered by Amit Y 5 · 0 0

simple.......2.121

2007-04-03 15:20:15 · answer #5 · answered by harry roger 1 · 0 0

fedest.com, questions and answers